2007
DOI: 10.2135/cropsci2006.09.0595
|View full text |Cite
|
Sign up to set email alerts
|

Aboveground Responses of Cool-Season Lawn Species to Nitrogen Rates and Application Timings

Abstract: Lawns are the largest managed turf acreage in the USA. This large acreage of fertilized turf has generated public concern regarding nitrogen (N) fertilizer misuse. This 2‐yr field study evaluated the effects of eight N programs that varied by N amount, 0 to 196 kg N ha−1 yr−1, and seasonal application timing on the aboveground plant responses of three cool‐season lawn species: Kentucky bluegrass (Poa pratensis L.; KBG), perennial ryegrass (Lolium perenne L.; PRG), and turf‐type tall fescue (Festuca arundinacea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
25
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 21 publications
7
25
0
Order By: Relevance
“…This supports the generally accepted observation that tall fescue requires less N than Kentucky bluegrass to produce acceptable turf quality (Teuton et al, 2007;Walker et al, 2007). On average, tall fescue required approximately 90% of the N concentration needed by Kentucky bluegrass for minimum and critical N concentrations.…”
Section: Kentucky Bluegrass Versus Tall Fescue Nitrogen Requirementssupporting
confidence: 83%
“…This supports the generally accepted observation that tall fescue requires less N than Kentucky bluegrass to produce acceptable turf quality (Teuton et al, 2007;Walker et al, 2007). On average, tall fescue required approximately 90% of the N concentration needed by Kentucky bluegrass for minimum and critical N concentrations.…”
Section: Kentucky Bluegrass Versus Tall Fescue Nitrogen Requirementssupporting
confidence: 83%
“…This 6‐year mean annual DM yield from an unamended control treatment is relatively large compared to that reported by others. Walker et al (34) reported turf‐type tall fescue annual DM yields of 1.17 and 0.84 tons/acre in 2004 and 2005, respectively, from a silt‐loam soil in Indiana with greater soil pH and organic matter and substantially less P in the topsoil than in this study. Over an 8‐year period, annual DM yield averaged 1.3 tons/acre for an unfertilized control treatment in northwest Arkansas on the same Captina silt‐loam soil as in this study (20).…”
Section: Forage Dry Matter Response To Litter Applicationmentioning
confidence: 40%
“…Nitrogen fertilization is therefore an important part of standard turfgrass management practices (Walker et al, 2007). Nitrogen fertilization is therefore an important part of standard turfgrass management practices (Walker et al, 2007).…”
Section: Nitrate Leaching and Nitrogen Fertilizationmentioning
confidence: 99%